2014
DOI: 10.1162/jocn_a_00473
|View full text |Cite
|
Sign up to set email alerts
|

Unconscious Automatic Brain Activation of Acoustic and Action-related Conceptual Features during Masked Repetition Priming

Abstract: Classical theories of semantic memory assume that concepts are represented in a unitary amodal memory system. In challenging this classical view, pure or hybrid modality-specific theories propose that conceptual representations are grounded in the sensory-motor brain areas, which typically process sensory and action-related information. Although neuroimaging studies provided evidence for a functional-anatomical link between conceptual processing of sensory or action-related features and the sensory-motor brain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 92 publications
13
25
1
Order By: Relevance
“…These differences compared to the study in nouns may reflect interindividual variation in brain anatomy of the different samples or the use of material from different lexical classes (see also the General Discussion section). For each scalp region, repeated-measures analyses of variance (ANOVA) were performed on mean voltages within three time windows: 180–280, 280–380, and 380–480 ms similar to earlier studies (Kiefer et al, 2008; Trumpp et al, 2013b, 2014). In a first step, the analyses of variance (ANOVAs) included the factors scalp region (centro-parietal, fronto-central), feature type (sound, action, control words), hemisphere (left, right), and electrode site.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…These differences compared to the study in nouns may reflect interindividual variation in brain anatomy of the different samples or the use of material from different lexical classes (see also the General Discussion section). For each scalp region, repeated-measures analyses of variance (ANOVA) were performed on mean voltages within three time windows: 180–280, 280–380, and 380–480 ms similar to earlier studies (Kiefer et al, 2008; Trumpp et al, 2013b, 2014). In a first step, the analyses of variance (ANOVAs) included the factors scalp region (centro-parietal, fronto-central), feature type (sound, action, control words), hemisphere (left, right), and electrode site.…”
Section: Methodsmentioning
confidence: 99%
“…Using ERP recordings, the present work aimed at assessing whether feature-specific ERP differences between action and sound concepts, as previously observed in nouns (Trumpp et al, 2013b, 2014), can be found within the word class of verbs. Furthermore, as effector-specific activation in action verbs has not always been replicated (Postle et al, 2008; Arévalo et al, 2012) the assessment of category effects across feature types such as action vs. sound would be a promising novel approach to test grounded cognition theories in the domain of verbs.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…First, although task conditions may suppress it, motor system activation whilst processing action-related stimuli is manifest even if participants do not actively attend to language input (Grisoni et al, 2016;Moseley, Pulvermü ller, & Shtyrov, 2013;Pulvermü ller, Shtyrov, et al, 2005;Shtyrov et al, 2004Shtyrov et al, , 2014Trumpp, Traub, & Kiefer, 2013;Trumpp, Traub, Pulvermü ller, & Kiefer, 2014). Second, motor activation during processing of action language is flexible, following the pattern expected for semantic mechanisms (for discussion, see .…”
mentioning
confidence: 99%